Fluorinated Interfaces for Efficient and Stable Low‐Temperature Carbon‐Based CsPbI2Br Perovskite Solar Cells. (7th July 2022) - Zhang, Xiang; Zhang, Dan; Zhou, Yuan; Du, Yunxiao; Jin, Junjun; Zhu, Zhenkun; Wang, Zhen; Cui, Xiaxia; Li, Jinhua; Wu, Sujuan; Zhang, Jing; Tai, Qidong
Abstract: Carbon‐based inorganic perovskite solar cells (C‐PSCs) have attracted intensive attention owing to their low cost and superior thermal stability. However, the bulk defects in perovskites and interfacial energy level mismatch seriously undermine their performance. To overcome these issues, a multifunctional dual‐interface engineering is proposed with a focus on low‐temperature CsPbI2 Br C‐PSCs, where the potassium trifluoroacetate (KTFA) and the 4‐trifluorophenyl methylammonium bromide (CF3 PMABr) are introduced beneath and on top of the perovskite layer, respectively. It is found that TFA ‐ ions locate at the SnO2 /CsPbI2 Br interface, whereas a small amount of K + ions diffuse into perovskite lattice to participate in nucleation and crystallization, resulting in more favored interfacial energy level alignment, improved film quality, passivated interfacial defects, released interfacial strain, as well as suppressed charge recombination and ion migration. Meanwhile, the CF3 PMABr passivates I/Br vacancies and forms 2D perovskite capping layer to facilitate hole extraction at the CsPbI2 Br/carbon interface. As a result, a remarkable power conversion efficiency (PCE) of 14.05% with an open‐circuit voltage of 1.273 V is achieved. To the best of the authors' knowledge, it is currently the highest PCE reported for low‐temperature CsPbI2 Br C‐PSCs. Furthermore, the nonencapsulated device exhibits improved moisture, thermal, and illumination stability in ambient air. Abstract : In this study, a fluorinated dual‐interface design is proposed for low‐temperature carbon‐based CsPbI2 Br perovskite solar cells by applying potassium trifluoroacetate as cathode interlayer and 4‐trifluorophenyl methylammonium bromide as anode passivation layer. As a result, the optimized device achieves the highest efficiency of 14.05% and improved moisture, thermal, and illumination stability in ambient air.